Manajemen risiko perbankan syariah dalam menghadapi tantangan global - AZZAM, MUHAMMAD (Maliki Interdisciplinary Journal, 2025)
Islamic banking, as an integral part of the national financial system, faces various complex global challenges, including economic volatility, the advancement of digital technology, and increasing risks related to Sharia compliance. In this context, risk management becomes a key element in maintaining the stability and sustainability of Islamic banking operations. This study aims to conceptually examine how risk management strategies are implemented in Indonesian Islamic banks in response to global dynamics. The discussion covers an understanding of the characteristics of risks within the Sharia-based system, global challenges that affect bank performance, and applicable risk mitigation strategies. The findings indicate that an adaptive, integrated, and Sharia-compliant approach to risk management is essential to strengthen the resilience of Islamic banks. Furthermore, strengthening the role of the Sharia Supervisory Board, optimizing technology, and improving human resource competence are strategic steps in addressing future challenges. With effective risk management, Islamic banking is expected to grow sustainably and contribute significantly to the national economy.